Dietary supplemental xylooligosaccharide modulates nutrient digestibility, intestinal morphology, and gut microbiota in laying hens - Zhou, Jianmin; Wu, Shugeng; Qi, Guanghai; Fu, Yu; Wang, Weiwei; Zhang, Haijun; Wang, Jing (Animal Nutrition, 2021)
This study was conducted to evaluate the prebiotic effects of dietary xylooligosaccharide (XOS) supplementation on performance, nutrient digestibility, intestinal morphology, and gut microbiota in laying hens. In a 12-wk experiment, a total of 288 Hy-Line Brown layers at 50 wk of age were randomly assigned into 3 dietary treatments supplemented with XOS at 0, 200 or 400 mg/kg. Each treatment had 8 replicates with 12 birds each. Hens fed XOS diets showed a lower feed-to-egg ratio during wk 7 to 12 and a higher egg yolk color value in wk 12 compared with those fed the control diet (P < 0.05). Dietary XOS supplementation improved the apparent total tract digestibility of gross energy and nitrogen at the end of the 12th wk (P < 0.05). In addition, a higher villus height-to-crypt depth ratio of the ileum was observed in XOS-added groups (P < 0.05). The high throughput sequencing analysis of bacterial 16S rRNA revealed that dietary XOS supplementation at 200 mg/kg altered cecal microbiota. Alpha diversity analysis illustrated a higher cecal bacterial richness in birds fed with XOS at 200 mg/kg. The composition of cecal microbiota modulated by the XOS addition was characterized by an increased abundance of Firmicutes along with a reduced abundance of Bacteroidetes. At the genus level, dietary XOS supplementation triggered decreases in Bacteroides and Campylobacter concurrent with increases in Lactobacillus and several short chain fatty acid producers including Desulfovibrio, Faecalitalea, Faecalicoccus, and 5 genera of family Lachnospiraceae. Collectively, dietary XOS addition improved the feed conversion ratio by modulating nutrient digestibility and ileal morphology in laying hens, which could be attributed to the enhancement of bacterial diversity and alteration of microbial composition.